The Relationship between Folic Acid and Vitamin B12 Serum Levels with High Sensitivity C-reactive Protein and Homocysteine in Chronic Hemodialysis Patients: A Cross-sectional Study - Aida Lydia; Dimas Priantono; Kuntjoro Harimurti; Idrus Alwi (Acta Medica Indonesiana)
Background: Folic acid (FA) and vitamin B12 treatment have been routinely prescribed to lower serum homocysteine levels and to reduce inflammation. However, no study has been conducted to determine serum folic acid (SFA) and vitamin B12 (B12) levels in patients who have twice-weekly hemodialysis. The aim of our study was to assess serum folate and B12  levels in chronic hemodialysis patients and their relationship with hsCRP and homocysteine levels. Methods: Our study was a cross-sectional study involcing patients who had twice-weekly hemodialysis in Dr Cipto Mangunkusumo National Hospital Jakarta, Indonesia. Predialysis blood samples were taken to measure SFA, B12, homocysteine and hsCRP levels. Patients with medical conditions affecting the assays were excluded. Spearman correlation was used to compare variables. Results: Eighty subjects enrolled in this study. Among those of non-given folic acid and vitamin B-12 supplementation, only 3.85% of subjects had low folic acid levels, and none had low vitamin B12 levels. A moderate negative correlation between serum folic acid and homocysteine level (p≤0.001; r=-0.42) and a weak correlation between serum vitamin B12 and homocysteine level (p=0.009; r=-0.29) was found. Among the high-risk cardiovascular group (CRP>3, n=49), there is a moderate negative correlation between serum folic acid and homocysteine level (p≤0.001; r=-0.561) and a weak negative correlation between vitamin B12 and homocysteine level (p=0.018; r=-0.338). Conclusion: There is a significant negative correlation between serum vitamin B12 and folic acid with homocysteine levels, especially in high-risk cardiovascular group.